Culturing and Imaging Glioma Stem Cells in 3D Collagen Matrices. Issue 1 (4th January 2023) - Cowan, James M.; Juric, Matey; Petrie, Ryan J.
Abstract: Methods to maintain human glioma stem cells as neurosphere cultures and image their dynamic behavior in 3D collagen matrices are described. Additional approaches to monitor glioma stem cell differentiation into mesenchymal‐type cells, along with example data are included. Together, these approaches enable glioma stem cell differentiation to be controlled while maintaining the cells in culture, as well as allowing cell dynamics to be captured and analyzed. These methods should be helpful for those seeking to understand the molecular mechanisms driving the invasion of glioma cells through three‐dimensional environments. © 2023 Wiley Periodicals LLC. Basic Protocol 1 : Culturing human glioma stem cells as neurospheres Basic Protocol 2 : Inducing GSC adherence and monitoring their differentiation into mesenchymal cells Support Protocol 1 : Preparing fibronectin‐coated dishes for cell microscopy Basic Protocol 3 : Embedding GSCs in a 3D collagen matrix to study their invasive behavior Support Protocol 2 : Phase‐contrast imaging with a tiled matrix to study cell migration in a 3D gel